PENGARUH MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALLY TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS PESERTA DIDIK KELAS XII IPS SMAN 3 PADANG - Syafitry, Widya; Asmar, Ali (Jurnal Edukasi dan Penelitian Matematika, 2024)
This study aims to test whether students who learn using the Somatic, Auditory, Visualisation, Intellectually (SAVI) model have better ability to represent than students who learn with direct learning. Quasi-experiment with Static Group Design is employed. This study include 2023/2024 grade XII IPS SMA N 3 Padang students. The final test and quizzes assessed mathematical representation skills. P-value of 0,000 with an actual level of 0,05 rejects H0 in hypothesis testing. This suggest that SAVI students have superior mathematics representation skills than Direct students. Therefore, learning with the SAVI approach affects students mathematics representation skills.Keywords– Somatic, Auditory, Visualization, Intellectually; Mathematical Representation Skills; Direct Learning